OLD BEMORALTY (OLDER COMMUNITY BEING MORE HEALTHY) IMPROVEMENT EFFORTS THROUGH INDEPENDENCE ELDERLY POSYANDU BASED ON HIERARCHICAL CLASS SYSTEM OF ABRAHAM MASLOW - M. Hasinuddin; Sofi Yulianto; M. Suhron (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2015)
Introduction. Aging is a natural process in humans is accompanied by a decrease in the physical, psychological and social which interact with each other is known as the elderly. The purpose of this study was to determine the effectiveness of the Elderly Posyandu using Abraham Maslow hierarchy of the class system of the elderly independence. Method. The design of this study was quasy experiment with post-test only with control group design. Data collection was performed using the independence of elderly people who modifi ed checklist sheet of cards to health (KMS) elderly and then test hypothesis test using independent t test with signifi cance level 0.05. Results. Statistical analysis showed the independence of the elderly for the treatment group obtained a mean value of 75.4615 and 60.8462 of the control group. Normality test as a condition of the t test showed the two groups has a normal distribution so as to know the difference between the independence of elderly people treated group and the control group were tested using independent t test with p value = 0.001 results < α (0.05). There was a difference in elderly independence between the treatment and control groups. Discussion. Need for innovative program to improve the independence of the elderly through the integration of health services through Posyandu modifi ed by taking into account the biological, psychological, social, and spiritual based class Maslow hierarchy. Keywords: Elderly, Posyandu, independence, Maslow